Development of Student Worksheets on Dynamic Fluids Material to Improve Science Literacy - Isnaniah, Rizki Maulidia; Miriam, Sarah; Suyidno, Suyidno; Qamariah, Qamariah (Universitas Lambung Mangkurat, 2024)
Science literacy is one of the skills and competencies needed in physics learning. However, literacy skills need to be well-practised and have received little attention from schools. This research aims to develop science literacy-based student worksheets that are valid, practical, and effective and, therefore, appropriate for improving students' science literacy. This development study uses the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The study used a one-group pre-test and post-test method with 35 students from class XI MIPA 4 at SMAN 8 Banjarmasin. Data collection instruments included validation, lesson plan observation sheets, and learning outcome tests. Data analysis techniques involved calculating the average score on validation and practicality results, which were then analyzed descriptively based on achievement categorization. The effectiveness analysis used the N-Gain formula. The research results indicate that (1) The student worksheets and learning outcome tests are valid with excellent criteria; (2) The student worksheets and learning outcome tests are practical with excellent implementation criteria; (3) The student worksheets and learning outcome tests are effective, as indicated by an N-Gain science literacy score of 0.58, categorized as moderate. Based on these results, the science literacy-based physics worksheets on dynamic fluids material that were developed are declared feasible and can be used in the learning process to improve students' science literacy. The developed worksheets offer an alternative for enhancing students' science literacy.